English English - MOHLIM, MUHAMMAD FAUZAN MOHD; Nordin, Amir Haziq Bin; ROSLAN, RAIMI AFIF BIN; YAMIN, NUR KHALIDAH YASMIN BINTI KABUL; NUGRAHA, ANDHYKA TYAZ (Journal of Optimization System and Ergonomy Implementation, 2024)
This study takes a close look at Electric Cars (EVs) and Internal Combustion Engine Vehicles (ICEVs) in Malaysia to discover how they impact energy use, the economy, and the environment. This study is important because Malaysia is still a growing country with its own energy, economic, and environmental problems. It checks out how well Electric Vehicles (EVs) and Internal Combustion Engine Vehicles (ICEVs) work and how much power they need in various driving conditions. It does this by looking at the different types of energy used in Malaysia and how far car’s technology has comes. In terms of money, the study looks at how much both types of cars cost all together. The price of the car, the cost of repairs, the amount of gas used, and the effect of government support are all part of this. The study is mostly about how Electric Vehicles (EVs) and Internal Combustion Engine Vehicles (ICEVs) pollute and what effects they might have on the environment. This is to help Malaysia reach its goal of lowering greenhouse gas pollution. This study uses both data from the Malaysian government and data from other studies done in other countries. Statistics and comparisons are used to help with the study. The people who did the study think that the data will help us learn more about how people in Malaysia really feel about Electric Vehicles (EVs) and Internal Combustion Engine Vehicles (ICEVs). Customers, lawmakers, and people who work in the business will all be able to choose more eco-friendly ways to get around thanks to these results.